Seasoldier Surabaya’s Meaning-Making of Environmental Issues - Nadiya Tri Aryani; Fidela Narasyah Ervan; AR Zamam Lubab; Andjani Antonetha Peni; Azha Hafidzha Husen; Arunil Izzah (Jurnal Ecopsy, 2026)
Climate change and the broader environmental crisis underscore the importance of community engagement in fostering environmental awareness and pro-environmental behavior. This study examined how members of Seasoldier Surabaya interpret environmental issues through their participation in community activities. The study adopted a qualitative design and applied Interpretative Phenomenological Analysis (IPA). Data were collected through semi-structured, in-depth interviews with two Generation Z members of Seasoldier Surabaya who had actively participated in community activities for at least one year. The findings showed that members perceive their involvement in Seasoldier Surabaya not merely as participation in environmental action, but also as a personal and social experience that strengthens concern for environmental issues. Community engagement generates emotional satisfaction, a sense of belonging, and social support, while also reshaping members’ perspectives on the relationship between the self, others, and the environment. This involvement further strengthens their commitment to sustaining pro-environmental behavior over time. In addition, the community’s egalitarian and supportive structure plays a central role in maintaining consistent member engagement. These findings suggest that interpretations of environmental issues emerge through collective experiences that are internalized within the community context.